Effects of Yeast Weight and Starter Volume on The Percentage Kepok Banana Based Bioethanol - Kurnia Dewi Budi Cantika; Anisa Sinta Nabila; Difa Afiyah Sucisatryani (Universitas Pakuan, 2021)
The low availability of energy resources is in line with the increasing human need for these resources, such as fossil fuels which are increasingly expensive because they are difficult to obtain right. Bioethanol is an environmentally friendly liquid produced from the glucose fermentation process from carbohydrate sources of natural raw materials with the help of microorganisms in baker's yeast. The focus of the research is on the waste of kepok banana peels because it has a high starch content of 18.5%. In addition, kepok banana peel waste is easy to obtain and has not been widely used by the community. This study aims to determine the effect of yeast weight and starter volume in the manufacture of bioethanol and the quality of the bioethanol produced by comparing the levels with the reference levels of bioethanol as an alternative fuel. The bioethanol obtained from the starch of the kepok banana peel has gone through a fermentation process with Saccharomyces cerevisiae and refined into pure bioethanol. Based on the related literature review, it shows that the greater the weight of yeast and the volume of starter used in the manufacture of kepok banana peel bioethanol influences the yield of bioethanol content which also increases so that it affects the quality of the bioethanol produced. However, the level of bioethanol that is obtained has not reached the standard range of SNI 7390:2012 with a minimum level of bioethanol as a substitute for fuel being 94.0-95.5%. Thus, bioethanol cannot be used as a substitute for fossil fuels and further research is needed with the use of the optimum amount of yeast and starter volume and re-purification.